PENILAIAN ASET MESS ITOGAPURA MILIK PEMERINTAH DAERAH KABUPATEN HALMAHERA TENGAH TAHUN 2014 - ARSYAD, INDRA AYU R.A ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research is to determine a reasonable the Mess of Itogapura Gamtofkange by located in urban villages, Tidore sub-district, on Tidore island with 4,827 square meters and building consist of 868 square meters by using methods of Depreciated Replacement Cost (DRC). Determine the cost of new building, so this method is applicable in the reproduction cost new building after deducting depreciation, where's depreciation methods is used to determine the method of straight lines, and then by added by value of the land, that was obtained by comparison sales method. Primary data was used to get various of information on property (land and building) by direct investigating to obtain actual data about the assets was surveyed. The process of data primary was done unstructured interview with a guard of object building to get general profile, that next done measurement extent of land and buildings and several documentary about mess of Itogapura, there were 3 data comparison. Secondary data was obtained the data of several working (Unit of local government) related, the data obtained such as certificate, RTBL (planning of buildings and environments) of Tidore islands, RTRW (spatial plan) year 2013-2033, guidelines the standard unit of prices of goods and services 2014, the calculation of inflation Tidore island, Central Halmahera in figures 2013. The result analysis on objects was conclude that indicate of reasonable value has been recorded in financial report of region district of central government of Halmahera on assets (land and building) with details land value Rp825.420.000,00 and value of building Rp1.883.560.000,00 with value property Mess of Itogapura was Rp2.708.980.000,00. The assessment of object can be explained too, that there was differences distance a part of value taht recorded in the financial balance sheet of Halteng district report currently, where was difference the 8,55 times from initial price. The differences with the NJOP and judgment results on land and building was as much as 52,43 percent or about Rp1.420.200.000,00. Keywords: Depreciated Replacement Cost (DRC), property specifically, reproduction cost new, depreciation, and value of land